Development And Validation of Redeemer’s University Psychological Distress Questionnaire (Rupdq) - Oladejo , Ademola Sikiru; Oladejo , Ademola Sikiru; Akpunne , Bede Chinonye; Mopa-Egbunu, Adenike; Olasubomi Olatunde Ahmed; Olufunmilayo Taiwo Janet; Ayoade, Ololade Titilola (Corpus Intellectual, 2025)
The Redeemer's University Psychological Distress Questionnaire (RUPDQ), a fourteen-item diagnostic instrument, was validated among residents of Osogbo/Owode Ede community, Osun State, Nigeria. An initial set of thirty items for the Redeemer's University Psychological Distress Questionnaire (RUPDQ) were created based on the clinical features of psychological distress in both the DSM and ICD, as well as a review of theories of psychological distress. After that, the items were reviewed by ten experts, eight clinical psychologists, one developmental psychologist, and one industrial/organizational psychologist with at least ten years of expertise in the field. A Yes/No nominal scale's Content Validity Ratio (CVR) was used to assess the items. Using the 70% item inclusion, 28 items were retained while the remaining two items were discarded. The 28 PDQ items were subjected to an Exploratory Factor Analysis (EFA). The first step of the EFA procedure involved extracting factors with eigenvalues greater than one. The sampling adequacy KMO value, as indicated by Table 1, was .80, falling within the recommended range of 0 to 1. There was a significant BTS (X2 = 7748.07, df= 378, p =.000). Consequently, the Principal Components Analysis (PCA) was performed, and the outcomes confirmed that the correlation matrix was factorable. Seven components were identified with eigenvalues > 1 according to the main component extraction method's test. The results of the study showed that the 14-item PDQ had good internal consistency and validity scores to measure psychological distress. The Psychological Distress Questionnaire is reliable and valid when used with Nigerian people, according to this study.